Do firms demand temporary workers when they face workload fluctuation? Cross-country firm-level evidence on the conditioning effect of employment protection - Vanessa Dräger; Paul Marx (Institute for the Study of Labor (IZA), 2012)
Although the negative economic effects of temporary employment are widely discussed, cross-country research on firms' demand for temporary employment is rare. National studies indicate that workload fluctuations are one major motive for firms to employ temporary workers. By studying a novel data set of 18,500 firms from 20 countries, we show that workload fluctuations increase the probability of hiring temporary workers by eight percentage points in rigid labour markets, but no such effect is observed in flexible labour markets. This conditioning effect of employment protection is in line with a recently developed search-and-matching model. Our results are robust to subgroups, subsamples and alternative estimation strategies.
Keywords: J23; J28; J21; J63; J68; J82; 330; temporary employment; employment protection; labour demand; firm-level data; Befristeter Arbeitsvertrag; Arbeitsnachfrage; Kapazitätsauslastung; Konjunktur; Arbeitnehmerschutz; Arbeitsmarktflexibilität; Schätzung; Welt